Conversion of Natural Jordanian Kaolin into Zeolite A without Thermal Pre‐activation. Issue 8 (27th March 2014) - Gougazeh, Mousa; Buhl, Josef‐Christian
Abstract A method for converting natural Jordanian kaolin without thermal pre‐activation into a synthetic zeolitic molecular sieve, known as zeolite A, is presented. All previous efforts to convert the kaolin into zeolite A have involved the use of high temperature or expensive minerals or organic acids. Natural Jordanian kaolin and citric acid were used under these conditions for the first time and reaction parameters were optimized. In this approach, an optimized low temperature zeolite synthesis process is performed for production of zeolite A of suitable quality at interesting commercial conditions. The process comprises direct alkaline conversion of natural kaolin into hydroxysodalite, subsequent to dissolving the hydroxysodalite in a dilute acid, prior to crystallization of zeolite by adding alkali hydroxide. After sodalite formation, aqueous base is added to the whole slurry until the pH exceeds 12 and a zeolite precursor gel is formed. The resulting precursor gel is aged for 4 h at a temperature of 100 °C to form a zeolite of type A. Zeolite made in accordance with the presented approach may be used as chemicals, molecular sieves, and catalyst. The obtained products were characterized with powder X‐ray diffraction, Fourier transform Infrared spectroscopy, scanning electron microscopy, differential thermal analysis, and thermogravimetric analysis. The results showed that zeolite A is formed together with residual amorphous silica resulting from the quartz fraction in the kaolin. The morphology of the obtained zeolite A could be seen as well crystallized with cube shape.